HUBUNGAN MEROKOK DAN OLAHRAGA DENGAN KEJADIAN HIPERTENSI DI JORONG GANDO WILAYAH KERJA PUSKESMAS PANINGGAHAN KABUPATEN SOLOK - Netty Herawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Hypertension as a risk factor for death in the world. The World Health Organization (WHO) states that tobacco kills more than five million people per year and is projected to kill 10 million by 2020. Patients with hypertension in 2017 in the Paninggahan Community Health Center are 984 (8.06%), while hypertension sufferers per jorongnya three months the last in the Paninggahan Puskesmas Work Area was obtained the highest Jorong Gando as many as 31 people. This type of research is descriptive with cross sectional design. In this study the independent variables are smoking and exercise, the dependent variable is the incidence of hypertension. Based on the results of a study conducted in January 2018 of 31 respondents, it was found that the results of more than a portion (58.1%) of respondents experienced mild hypertension, more than half (54.8%) did not smoke, more than a portion (51.6%) ) respondents do not do regular exercise, there is no relationship between respondents who have the habit of smoking with the incidence of hypertension and there is no relationship between sports with the incidence of hypertension in jorong Gando in the Work Area of Paninggahan Health Center, Solok.